2012
DOI: 10.1080/19425120.2012.675983
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Management of Black Sea Bass: Influence of Biogeographic Barriers on Population Structure

Abstract: The black sea bass Centropristis striata is a commercially important perciform fish with a general distribution along the U.S. Atlantic coast from Cape Cod, Massachusetts, to Cape Canaveral, Florida, and in the Gulf of Mexico from Mobile Bay, Alabama, to Tampa Bay, Florida. Currently, black sea bass are managed as three separate stocks: one in the Gulf of Mexico and two along the U.S. Atlantic coast. Fish from the Gulf of Mexico represent a separate subspecies, C. striata melana. The Atlantic subspecies, C. st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Although this study included observations from thousands of captured Black Sea Bass, sample sizes for the analysis of sex change rates were smaller and should be considered when planning future tagging studies. The present observations have important implications for stock assessment of mid-Atlantic Black Sea Bass, but these specific life history findings could vary geographically because the maximum size of Black Sea Bass varies with latitude (Wuenschel et al 2011) and because regional populations vary in life history and morphology (Roy et al 2012). Future studies should focus on evaluating the size at sex change and the transition rates in Black Sea Bass occurring in regions outside of the mid-Atlantic.…”
Section: Seasonality Of Sex Changementioning
confidence: 72%
See 1 more Smart Citation
“…Although this study included observations from thousands of captured Black Sea Bass, sample sizes for the analysis of sex change rates were smaller and should be considered when planning future tagging studies. The present observations have important implications for stock assessment of mid-Atlantic Black Sea Bass, but these specific life history findings could vary geographically because the maximum size of Black Sea Bass varies with latitude (Wuenschel et al 2011) and because regional populations vary in life history and morphology (Roy et al 2012). Future studies should focus on evaluating the size at sex change and the transition rates in Black Sea Bass occurring in regions outside of the mid-Atlantic.…”
Section: Seasonality Of Sex Changementioning
confidence: 72%
“…Our results are applicable to mid-Atlantic Black Sea Bass, but their applicability to populations in the south Atlantic and Gulf of Mexico is unknown due to differences in life histories and potential for geographic variation in gonad development. Genetic analyses have shown that Gulf of Mexico Black Sea Bass represent a separate subspecies, C. striata melana, and there is sufficient genetic variability between the northern (mid-Atlantic) and southern (south Atlantic) stocks along the East Coast to support the occurrence of distinct Black Sea Bass populations in the three regions (Roy et al 2012). Studies of sex change in each population indicate that gonad development may vary geographically.…”
Section: Seasonality Of Sex Changementioning
confidence: 99%
“…Across the species' range, persistent genetic differences are evident between Atlantic populations north and south of Cape Hatteras, as well as between the Atlantic Ocean and Gulf of Mexico (Bowen and Avise 1990;Roy et al 2012;McCartney et al 2013). South of Cape Hatteras Black Sea Bass are smaller and nonmigratory (Wenner et al 1986;Hood et al 1994); this southern stock is managed by the South Atlantic Fishery Management Council, as part of their snapper-grouper complex (SAFMC 2013).…”
Section: Striped Bass and Black Sea Bassmentioning
confidence: 99%
“…(1) mitochondrial DNA polymorphisms exist within the exploitable stock from North Carolina to Massachusetts (McCartney et al 2013), (2) ecophenotypes exist and are observable with meristic and morphometric characters (Shepherd 1991), and (3) different migratory contingents exist and either migrate northsouth between the northern and southern portions of the Middle Atlantic Bight or undertake shorter, onshore-offshore migrations within the southern portion of the bight (Musick and Mercer 1977;Hood et al 1994;Moser and Shepherd 2009). Across the species' range, persistent genetic differences are evident between Atlantic populations north and south of Cape Hatteras, as well as between the Atlantic Ocean and Gulf of Mexico (Bowen and Avise 1990;Roy et al 2012;McCartney et al 2013). South of Cape Hatteras Black Sea Bass are smaller and nonmigratory (Wenner et al 1986;Hood et al 1994); this southern stock is managed by the South Atlantic Fishery Management Council, as part of their snapper-grouper complex (SAFMC 2013).…”
Section: Striped Bass and Black Sea Bassmentioning
confidence: 99%
“…Black sea bass, a demersal species in the family Serranidae, are found along the Atlantic coast from Massachusetts to Florida, USA, and in the Gulf of Mexico (Collette & Klein-MacPhee 2002). Three stocks are currently recognized: Gulf of Mexico, south Atlantic Bight, and mid-Atlantic Bight (Roy et al 2012); the latter is the focus of this study. Like other temperate reef fishes, black sea bass are typically associated with hard bottom structures such as reefs and rock outcroppings.…”
Section: Introductionmentioning
confidence: 99%